Application of Hypertension Using Poster Media for Pharmacy Visitors - Betty Sunaryanti (Public Health and Safety International Journal, 2022)
The results of a preliminary study show that the prevalence of hypertension in XYZ Pharmacy is 5.00% in 2021. However, health promotion efforts have not been carried out on this problem. One of the media that can be used for health promotion is posters. The formulation of the research problem is how the interest and understanding of visitors to Apotek xyz towards hypertension poster media is seen from the design, message content and place of installation. The purpose of the study was to determine the interest and understanding of visitors to the xyz pharmacy. The research method used is descriptive qualitative with phenomenological design. The subjects in this study were visitors to the xyz pharmacy. Another informant is a health promotion officer who is the Head of the Pharmacy. Data was collected through focus group discussions (FGD), in-depth interviews, and observations. The results showed that overall, most of the visitors were interested in and understood the hypertension poster. The Sundanese version of hypertension poster is more accepted as a health promotion medium by pharmacy visitors who have an interest in the design and content of the message in the hypertension poster. The conclusion of the study is that pharmacy visitors are interested and can understand hypertension posters..